The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/pits.22136
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing executive function skills in preschoolers through a mindfulness‐based intervention: A randomized, controlled pilot study

Abstract: Executive functions (EFs) develop rapidly in preschoolers and lay an important foundation for school readiness. One potential method of supporting EF development is through mindfulness‐based interventions (MBIs). Whereas studies with older children and adults have supported this approach, research with young children has been more limited. In the current study, we evaluated the effectiveness, acceptability, and feasibility of Mini‐Mind, a 12‐session MBI created specifically for preschoolers. We used a randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 30 publications
(97 reference statements)
0
34
0
Order By: Relevance
“…Seven studies (Crooks et al, 2020 ; Jackman et al, 2019 ; Lemberger-Truelove et al, 2018 ; Li-Grining et al, 2021 ; Poehlmann-Tynan et al, 2016 ; Thierry et al, 2016 ; Zelazo et al, 2018 ) indicated that participants lived in economically disadvantaged communities, and one study recruited participants from a high trauma community (Razza et al, 2020 ). Though not all studies reported the types of early childhood programs, three studies were conducted in federally funded or subsidized preschools (Li-Grining et al, 2021 ; Jackman et al, 2019 ; Poehlmann-Tynan et al, 2016 ) and one study focused on a university based early childhood center (Wood et al, 2018 ). Five studies indicated that the majority of the participants were bilingual Hispanic or Latin X children (Lemberger-Truelove et al, 2018 ; Li-Grining et al, 2021 ; Moreno-Gómez and Cejudo, 2019 ; Thierry et al, 2016 ; Thierry et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies (Crooks et al, 2020 ; Jackman et al, 2019 ; Lemberger-Truelove et al, 2018 ; Li-Grining et al, 2021 ; Poehlmann-Tynan et al, 2016 ; Thierry et al, 2016 ; Zelazo et al, 2018 ) indicated that participants lived in economically disadvantaged communities, and one study recruited participants from a high trauma community (Razza et al, 2020 ). Though not all studies reported the types of early childhood programs, three studies were conducted in federally funded or subsidized preschools (Li-Grining et al, 2021 ; Jackman et al, 2019 ; Poehlmann-Tynan et al, 2016 ) and one study focused on a university based early childhood center (Wood et al, 2018 ). Five studies indicated that the majority of the participants were bilingual Hispanic or Latin X children (Lemberger-Truelove et al, 2018 ; Li-Grining et al, 2021 ; Moreno-Gómez and Cejudo, 2019 ; Thierry et al, 2016 ; Thierry et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since this comprehensive meta-analysis there have been three further studies evaluating the effectiveness of a mindfulness intervention in young children. Wood et al (2018) evaluated a mindfulness intervention delivered by specialist facilitators to preschoolers (age 3–5 years; n = 12) compared to a control condition ( n = 15). Outcomes were assessed using a purpose-designed teacher report questionnaire that assessed five components of EF as outlined by Miyake et al (2000).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study can be used to inform YMP programming in early childhood settings. In general, teachers in elementary [ 76 ] and early childhood settings [ 77 ] have indicated that YMP are feasible and acceptable to implement in educational settings. Education and childcare centers may also choose to integrate yoga and mindfulness practices within existing SEL programs.…”
Section: Discussionmentioning
confidence: 99%